SUELI CARNEIRO - ENGLISH VERSION - Bastos, Morgana Abranches; Mariz Lima, Geisa Louise (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Aparecida Sueli Carneiro was born in the city of São Paulo, on June 24, 1950. Her family background is of workers, she soon grew up in a family environment with community and sociable principles. A student at the Faculty of Philosophy at the University of São Paulo, his political activities, the black movement and black women, served as a basis for his militant training. She holds a PhD in Philosophy from the University of São Paulo (USP), in addition to being a philosopher, an activist in the anti-racist movement, a writer and one of the main thinkers of black feminism in Brazil.